Enalapril previne alterações cardiovasculares promovidas pelo tratamento crônico com doses suprafisiológicas de decanoato de nandrolona em ratos sedentários - Loiola, Leonardo Zanoteli (2011)
Nandrolone decanoate (ND) induces cardiovascular abnormalities, such as attenuation of the Bezold-Jarisch Reflex (BJR), cardiac hypertrophy and elevation of mean arterial pressure (MAP), and a relationship between androgens and the reninangiotensin system (RAS) has been reported. Objective: The purpose of this study was to evaluate the influence of RAS on the alterations in BJR, cardiac and prostatic hypertrophy and MAP evoked by ND. Methods: Male Wistar rats were treated with nandrolone decanoate (DECA; 10 mg/kg body.eight.week), and nandrolone plus enalapril (10 mg/kg body weight.day; DECAE) or vehicle (control animals; CON and CONE). After 8 weeks of treatment, the BJR was evaluated by bradycardia response elicited by serotonin administration (2–32 µg.kg-1 ). Mean arterial pressure (MAP) was assessed and cardiac hypertrophy was determined by the heart weight/body weight (HW/BW) ratio. Results: After eight weeks, Wistar rats treated with Nandrolone Decanoate showed increase on the mean arterial pressure, and enalapril was able to normalize it (CON = 98±1; CONE = 97±2; DECA = 109±2**; DECAE = 99±1 mmHg). This same behavior was verified on cardiac (CON = 2,52±0,05; CONE = 2,47±0,08; DECA = 2,78±0,06**; DECAE = 2,49±0,07) and prostatic (CON = 1,23±0,17; CONE = 1,23±0,09; DECA = 1,78±0,17**; DECAE = 1,36±0,14) hypertrophy. We also observed impairment in the BJR control of heart rate on the 8, 16 and 32 of 5-HT doses (S 8µg.Kg-1 : CON=-42±7%, CONE=-40±3%, DECA=-32±2%*, DECAE=- 41±2%; S 16µg.Kg-1 : CON=-54±4%, CONE=-55±6%, DECA=-44±2%, DECAE=- 53±2%; S 32µg.Kg-1 : CON=-71±3%, CONE=-68±2%, DECA=-59±2%, DECAE=- 68±2%, **p<0,01 *p<0,05 DECA animals related to CON, CONE and DECAE groups) and PAD on the 16 and 32 of 5-HT doses that also had been normalized in associated treatment with enalapril(S 16µg.Kg-1 : CON=-67±4%, CONE=-68±3%, DECA=-51±2%, DECAE=-63±3%; S 32µg.Kg-1 : CON=-81±2%, CONE=-75±3,2%, DECA=-62±3,1%, DECAE=-72±3,4%, **p<0,01 *p<0,05 DECA animals related to CON, CONE and DECAE groups). 13 Conclusions: Our results suggest that enalapril was able to normalize the MAP and the sensibility impairment of BJR, as well as prevent the development of cardiac and prostatic hypertrophy in rats whose alterations was resulted by nandrolone decanoate treatment.